IS THE RELATIVE AGE EFFECT PREVALENT IN ELITE BRAZILIAN MALE FUTSAL? AN INVESTIGATION BASED ON AGE CATEGORIES AND PLAYING POSITIONS (Kinesiology, 2022)
This study aimed to investigate the existence of relative age effect (RAE) in male Brazilian futsal athletes according to age categories and playing position. Data from male futsal athletes from the top five teams in Brazil were collected during May and June 2021. The distribution of birth dates of 387 male futsal athletes was analyzed, based on their age categories (U15, n = 97; U17, n = 88; U20, n = 116; senior, n = 86) and playing positions (defender, n = 76; winger; n = 162; pivot, n = 69; goalkeeper, n = 80). Chi-squared tests were used to analyze the birth dates distribution based on quarter and semesters of the year according to age categories and playing positions. The overall analysis of birth quarter indicated a higher occurrence of births in the first quarter of the year (p